The Central Pillar Technique: A New Septum-Based Pedicle Design for Reduction Mammaplasty - (:unkn) unknown (SAGE PUBLICATIONS INC, 2012)
Background: Successful breast reduction involves remodeling the breast parenchyma and creating a pedicle to maintain blood supply to the nipple-areola complex (NAC). Although vascular compromise is generally venous in breast reduction surgery, clear anatomical descriptions of the breast veins are lacking in textbooks. Objectives: The author designed an NAC flap based on arterial and venous territories defined in a cadaver study and subsequently assessed the technique in a series of live patients. Methods: Dynamic venous angiography was performed on hemithorax specimens from 6 fresh female cadavers. A new septum-based pedicle (the central pillar) was designed, which protected the periareolar vein polygon along with the breast septum. Sixty-seven patients underwent breast reduction with this technique between 2005 and 2010. Results: The patients were followed for an average of 26.4 months. Sixty-two of the 67 patients underwent bilateral reduction. The average reduction in tissue per breast was 910.7 g (range, 440-1935 g), and the average nipple transposition was 9.6 cm (range, 6-17 cm). The most common complications were delayed healing of the vertical puckered suture line (16 patients), seroma (7 patients), hematoma (2 patients), and unilateral deepithelialization of the NAC following transient venous congestion (2 patients). The patient satisfaction rate was high. Conclusions: The central pillar technique is a promising alternative for young patients with glandular breasts that require gross reduction and high-transposition NAC, who are not good candidates for the free nipple graft technique.
Keywords: gigantomastia; reduction mammaplasty; pedicle choice; breast surgery; NIPPLE-AREOLA COMPLEX; BREAST REDUCTION; LIGAMENTOUS SUSPENSION; CLINICAL IMPLICATIONS; VERTICAL MAMMAPLASTY; VENOUS DRAINAGE; DERMAL PEDICLE; MAMMARY-GLAND; TRANSPOSITION; TERRITORIES